The Efficacy and Safety of Metformin and Glimepiride Combination among Jordanian Patients with Type 2 Diabetes during Ramadan - Al-Saraireh, Yousef; Akour, Amal; Alhamydeh, Muyyed; Alfaqara, Alaaldeen; Al-Dalaen, Said; Al-Sarayreh, Sameeh; Rawashdeh, Arwa; Al-Shuneigat, Jehad (Jordan Journal of Pharmaceutical Sciences, 2020)
The Aims of the study: The prevalence of Type 2 diabetes mellitus (T2DM) is increasing worldwide including Islamic countries. Ramadan fasting increases risk of complications from T2DM especially hypoglycemia. The primary objective of the study was to assess glycemic control and incidence of hypoglycemia before, during and after Ramadan. Methods: One hundred adult Jordanian patients with Patients with T2DM who were on dual therapy with metformin and glimepiride and practice Ramadan were recruited. Glycemic control was assessed by HbA1c and fasting blood glucose (FBG), in addition to number of hypoglycemic episodes, before, during and after Ramadan. Results There was a significant decrease in HbA1cand FBG at the end of Ramadan compared to that before Ramadan (10.6±1.9 vs. 9.4±1.7 and 386.4±110) vs. 271.9 ±102.4; respectively). On the other hand, the number of hypoglycemic episodes was significantly less six to eight weeks after Ramadan than that during Ramadan (p<0.001), and those during Ramadan were significantly less than those prior to Ramadan. No statistically significant correlation (p>0.05) was detected between the number of hypoglycemic episodes and FBG or HbA1c at all visits. However, the percentage of patients with hypoglycemia during Ramadan was higher than that of after Ramadan (86% vs. 41%, p<0.01). Conclusion: While Ramadan fasting might be considered efficacious in patients with Patients with T2DM on combination of glimepiride and metformin, patients and/or their caregivers should be educated on the monitoring for signs and symptoms of hypoglycemia.